2012
DOI: 10.2216/10.87.1
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of carbon and phosphorus levels on the invasive cyanobacterium, Cylindrospermopsis raciborskii

Abstract: The invasive cyanobacterium, Cylindrospermopsis raciborskii, was cultured semicontinuously for 18 days at different carbon and phosphorus levels. Growth and photosynthesis were measured to study the combined effects of CO 2 and phosphorus availabilities. The results showed that enrichment of CO 2 or inorganic phosphorus (Pi) levels in the culture medium significantly increased specific growth rate (m), light-saturated photosynthesis (P m ) and photosynthetic efficiency (a), but tended to decrease dark respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A growing number of species reportedly do not grow more rapidly nor achieve higher cell densities in culture when CO2 concentrations are above ambient Czerny et al, 2009). Explanations range from CO2 saturation surrounding the carboxysome (even when environmental CO2 concentrations are low) via CO2concentrating mechanisms that are nearly ubiquitous among cyanobacteria, to growth limitations imposed by other nutrients or environmental factors (Beardall et al, 2009a;Czerny et al, 2009;Wu et al, 2012). Both of these mechanisms are pertinent to biocrusts in natural settings.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of species reportedly do not grow more rapidly nor achieve higher cell densities in culture when CO2 concentrations are above ambient Czerny et al, 2009). Explanations range from CO2 saturation surrounding the carboxysome (even when environmental CO2 concentrations are low) via CO2concentrating mechanisms that are nearly ubiquitous among cyanobacteria, to growth limitations imposed by other nutrients or environmental factors (Beardall et al, 2009a;Czerny et al, 2009;Wu et al, 2012). Both of these mechanisms are pertinent to biocrusts in natural settings.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the parameter E k , which indicates the onset of light saturated photosynthesis, has been measured to occur between 40 and 240 mmol photons (PAR) m À2 s À1 among different C. raciborskii strains and experimental conditions (Wu et al, 2009(Wu et al, , 2012Pierangelini et al, 2014b,c). Analysis of the photosynthetic apparatus also showed that an Australian strain of C. raciborskii (CS506) can potentially tolerate up to 425 mmol photons (PAR) m À2 s À1 (Pierangelini et al, 2014c) and Chinese strains between 900 and 1200 mmol photons (PAR) m À2 s À1 (Wu et al, 2009(Wu et al, , 2012Bai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Microalgal growth response included stimulations to bloom‐forming species when consumers were excluded (Fig. S6), with observed increases in biomass, cell abundance, population densities, and chlorophyll a in bloom‐forming Microcystis aeruginosa (Qiu and Gao ; Sandrini et al , b ), and increases in cell division rate, biovolume, growth rate, and chlorophyll a in bloom‐forming Cylindrospermopsis raciborskii under elevated CO 2 conditions (Wu et al ; Pierangelini et al ). Elevated CO 2 may thus worsen the impacts of algal blooms, although it is difficult to extend the results from the lab to the field.…”
Section: Resultsmentioning
confidence: 99%